Support Vector Machine Optimized by Henry Gas Solubility Optimization Algorithm and Archimedes Optimization Algorithm to Solve Data Classification Problems - Yu, Ji-Sheng; Zhang, Sheng-Kai; Wang, Jie-Sheng; Li, Song; Sun, Ji; Wang, Rui (Engineering letters, 2023)
Support vector machine (SVM) is the minimization of structural risk to construct a better hyperplane to maximize the distance between the hyperplane and the sample points on both sides of hyperplane. Two improved physics-wise swarm intelligence optimization algorithms (Henry gas solubility optimization algorithm and Archimedes optimization algorithm) were proposed based on Lévy flight operator, Brownian motion operator and Tangent flight motion operator to optimize the penalty factor and kernel function parameters of SVM so as to enhance its global and local search ability. Finally, the Iris datasets, Strip surface defect datasets, Wine datasets and Wisconsin datasets of breast cancer in UCI datasets were selected to carry out the simulation experiment. Simulation results show that optimizing SVM based on improved physical-wise swarm intelligence algorithms can effectively improve the classification accuracy.